Genomics of Developmental Plasticity in Animals - Lafuente, Elvira; Beldade, Patrícia (Frontiers in Genetics, 2019)
Developmental plasticity refers to the property by which the same genotype produces distinct phenotypes depending on the environmental conditions under which development takes place. By allowing organisms to produce phenotypes adjusted to the conditions that adults will experience, developmental plasticity can provide the means to cope with environmental heterogeneity. Developmental plasticity can be adaptive and its evolution shaped by natural selection. It has also been suggested that developmental plasticity can facilitate adaptation and promote diversification. Here we summarize current knowledge on the evolution of plasticity and on the impact of plasticity on adaptive evolution, and we identify recent advances and important open questions about the genomics of developmental plasticity in animals. We give special attention to studies using transcriptomics to identify genes whose expression changes across developmental environments, and studies using genetic mapping to identify loci that contribute to variation in plasticity and can fuel its evolution.